Usability Evaluation of a Google Sites-Based E-Learning Platform Using the ISO 9241-11:2018 Standard - Nurul Ikhsan; Sarmidi Sarmidi; Sulidar Fitri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to evaluate the usability of an e-learning system developed using Google Sites at SMA Negeri 6 Bengkulu Tengah based on the ISO 9241-11 standard. The evaluation focuses on two main aspects, namely effectiveness and user satisfaction. The research employed a quantitative descriptive method with data collected through questionnaires distributed to 30 students and 2 teachers. The results show that the effectiveness aspect achieved a percentage of 94.4% for teachers and 88.4% for students, both categorized as